Biogas from Cattle Dung as a Source of Sustainable Energy: A Feasibility Study - Kumar, K. Abhaya; Pinto, Prakash; Hawaldar, Iqbal Thonse; Kumar, B.R. Pradeep (International Journal of Energy Economics and Policy, 2020)
Many studies have stated that the usage of traditional cooking fuels like firewood, dung, and coal has caused many unfortunate deaths in India. The alternative fuel sources like LPG and electricity are in scarce and. Today, researches in the area of biofuel or bioenergy are of prime interest to many researchers to contribute to sustainable energy sources. Bioenergy from cattle dung is one such area, particularly for a country like India where dairy farms is a major supplier of feedstock. In this study, using logistic regression methodology, we have analysed the socio-economic factors influencing the adoption of biogas digesters among dairy farmers in Karnataka, India. The study revealed that the number of cattle and family size are the key factors for biogas adoption and poor knowledge of the family size and cattle ratio is the key hurdle. Using cross-tabulation and some basic mathematical analysis, we concluded that the optimal number of cattle for one adult in a family is 1. Keywords: Sustainable energy source, Biogas, Cattle dung, Dairy farmers, Socioeconomic factors, India JEL Classifications: Q4, P28 DOI: https://doi.org/10.32479/ijeep.10135